'Forever wars'? Patterns of diffusion and consolidation of Jihadism in Africa. (3rd April 2022) - Hansen, Stig Jarle
ABSTRACT: The article will discuss the patterns that jihadism has followed when spreading throughout sub-Saharan Africa, addressing the major scholarly debates but also to bring forward the elements that various African cases seemingly have in common. The discussions over African Jihadism has seen several great debates, over the ungoverned space theory, a dichotomous discussion of the local and the global as opposing explanatory models, and a discussion of the role of 'greed' and economic incentives. The article argues that these discussions need to be transcended, and that dichotomous discussions fail to see more complex patterns of interaction between various factors, and the complexity of social relations that at times depend on the different contexts we study. Understanding how global networks can harness local conflicts to gain support is key to understanding African jihadist groups, and how those harnessing strategies can be limited. The article also suggests that there is an emerging consensus over several of the factors that do occur in sub-Saharan African jihadism and present the implications of these findings for the ongoing conflict in Mozambique and Tanzania.